Microchemical Investigation of Long-Term Buried Gilded and Silvered Artifacts From Ancient Peru - Ingo, Gabriel M.; Albini, Monica; Bustamante, Angel D.; Zambrano Alva, Sandra del Pilar; Fernandez, Arabel; Giuliani, Chiara; Messina, Elena; Pascucci, Marianna; Riccucci, Cristina; Staccioli, Paola; Di Carlo, Gabriella; Tortora, Luca (Frontiers in Materials, 2020)
A large number of metal artefacts with exceptional artistic value of the Moche culture have been found in the tombs of the Lords of Sipán (Lambayeque, Peru) and of the Lady of Cao (El Brujo, Peru) characterised by different burial conditions. Some of the objects, dated around 300-400 AD, are constituted by substrates of Cu- or Ag-based alloys coated by uniformly distributed thin films of precious metal (1 - 4 microns) that create also polymetallic bicoloured surfaces with “gold” and “silver” areas. In order to investigate the corrosion product structure and composition as well as to identify the techniques used to give the gold or silver appearance, an integrated analytical approach has been adopted. The selected complementary methodologies were scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and optical microscopy (OM). The findings reveal that the substrates are mainly composed by Cu-Ag-Au alloys that at the site of Sipán have been almost completely corroded during the burial. Furthermore, the results show that the main aggressive agent is Cl- coming from the soil and that the degradation phenomena were likely enhanced by the galvanic coupling between the precious metal layer and the less noble substrate. The degradation products have formed mainly layered structures containing chloroargyrite (AgCl), cuprite (Cu2O), nantokite (CuCl), and atacamite (CuCl23Cu(OH)2) polymorphs. These latter species warn that dangerous copper cyclic corrosion is occurring, a harmful phenomenon, commonly defined as “bronze disease”, which must be be firmly mitigated. Finally, the findings reveal that the Moche metal workers used the depletion gilding to selectively modify the surface chemical composition of the artefacts to produce the Ag or Au thin films. According to this subtractive method, the surface of the Cu-Au-Ag alloys was enriched with a layer of precious metal by means of cycles of thermal treatments and removal of Cu or both Cu and Ag from the outermost region by using pickling solutions.